The euro area Bank Lending Survey matters: empirical evidence for credit and output growth - Gabe de Bondt; Angela Maddaloni; José-Luis Peydró; Silvia Scopel (European Central Bank (ECB), 2010)
This study examines empirically the information content of the euro area Bank Lending Survey for aggregate credit and output growth. The responses of the lending survey, especially those related to loans to enterprises, are a significant leading indicator for euro area bank credit and real GDP growth. Notwithstanding the short history of the survey, the findings are robust across various specifications, including “horse races” with other well-known leading financial indicators. Our results are supportive of the existence of a bank lending, balance sheet, and risk-taking channel of monetary policy. They also suggest that price as well as non-price conditions and terms of credit standards do matter for credit and business cycles. Finally, we discuss the implications for the 2007/2009 financial and economic crisis.
Keywords: C23; E32; E51; E52; G21; G28; 330; bank lending survey; business cycle; credit cycle; euro area; Monetary policy transmission; Kreditgeschäft; Konjunktur; Geldpolitik; Geldpolitische Transmission; Eurozone; EU-Staaten